Kedudukan Penggunaan Premisse Pada Akta Notaris Dalam Pelaksanaan Jabatan - Slamet, Lutfi Aldi Bing; Putra, Made Aditya Pramana (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 01 (2023), 2023)
Research purposes of this research is to determine the juridical review of the use of premissee on a notary deed in carrying out his position and also the role of a notary of a deed. This study use normative legal research method by using the statue approach and conceptual approach. Based on the result of this research of this study, it is concluded that the use of the premisse is still not regulated in law number 2 of 2014 concerning about theposition of a notary (UUJN) but the law only regulates the beginning of the deed, the body of the deed and the end or closing. In making a deed without using the premise of the deed that he made does not result in legal defects as long as it does not change contents of the deed and the role of the Notary in this case must be careful because if the Notary is negligent in making the deed. In carrying out his position, he will be held accountable and sanctioned in accordance with the laws and regulations. valid invitation. arrange a notary and its implementation in his office. Thus, a clearer regulation is needed regarding the premisse of the transaction in the authentic deed section in order to realize legal certainty and legal protection for the parties in the authentic deed.